Eficacia antimicrobiana del aceite esencial de Ruta graveolens (Ruda) sobre Staphylococcus aureus subesp aureus ATCCR 25904. - Montero Recalde, Mayra Andrea (2021)
The research aimed to evaluate the antimicrobial efficacy of the oil rue (Ruta graveolens) essential on the strain of Staphylococcus aureus subp aureus ATCC ®25904, the plant was collected from the Inapisí sector of the parish of Constantino Fernández, the oil obtained was through the method of hydrodistillation, 10 concentrations were evaluated (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%) in dilution with double distilled water, each dilution was handled with a total of 5ml and Tween 80 was added as 0.1% emulsifier, the The results showed that the determined Minimum Inhibitory Concentration of the essential oil was defined in 30%; and with respect to the Minimum Concentration Bactericidal evidenced by the zero growth of colonies on the plate, which is established at 40% concentration; the antimicrobial susceptibility study statistically required with the Tukey test at 0.5% significant differences between treatments, the best being at 90% concentration with 25.25 mm of formation of inhibition halos, despite treatments from 30% showed halos formation in an important way, concluding that the oil Ruta graveolens essential oil has antimicrobial efficacy on the strain evaluated at from 30% concentration.